(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Language is framed in many forms and functions. Flouting is one way to convey idea by deviating rule of communication named maxims that have been proposed by theorists before. The purpose of this study is to investigate the richness of language features used by the people of Papua in interacting ideas throughout TOB-CER program in RRI. The method used in this study was descriptive qualitative method. The procedures used to collect data were recording and selecting. Data was recorded for total seven nights and then selected the familiar topics by considering the distribution of woman and man broadcasters. The data then was transcribed into written forms. The reduction is needed to pick the needed text and then indexed the deviation of maxim quantity into the table. The collections of maxim quantity were analyze by using flouting as its benchmark. The results of this study showed that flouting of maxim quantity is usually used in telling joke and text of intertextuality. The features of telling joke/humor are to release tensions, holding friendship relations as aspect of humanity. Meanwhile, the intertextuality text is featured with measuring understanding and general status such as identity and power. The reasons to express all this flouting are to establish friendship, harmony and to grow the sense of belonging toward the existence of RRI as historical media communication in Papua.